1986
DOI: 10.1227/00006123-198605000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis Meningitis: A Report of Twelve Cases and a Literature Review

Abstract: Twelve recent cases of Mycobacterium tuberculosis meningitis were presented, and the literature was reviewed. There are no particularly new or unique therapies or approaches to the management of this most serious disease. The major obstacle to successful diagnosis and treatment of tuberculous meningitis continues to be a lack of clinical suspicion of its presence. As illustrated in the cases presented, it has been our experience that patients already moribund or nonresponsive do not respond, regardless of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(20 citation statements)
references
References 0 publications
1
17
0
2
Order By: Relevance
“…Hydrocephalus is a common complication of TBM; prevalence has been documented in >75% of patients in several published series [65, 66]. Ventriculoperitoneal shunt placement and endoscopic third ventriculostomy are surgical techniques which have been demonstrated to relieve elevated intracranial pressure (ICP) in TBM, leading to improved neurological outcomes [67, 68].…”
Section: Treatmentmentioning
confidence: 99%
“…Hydrocephalus is a common complication of TBM; prevalence has been documented in >75% of patients in several published series [65, 66]. Ventriculoperitoneal shunt placement and endoscopic third ventriculostomy are surgical techniques which have been demonstrated to relieve elevated intracranial pressure (ICP) in TBM, leading to improved neurological outcomes [67, 68].…”
Section: Treatmentmentioning
confidence: 99%
“…In a previous study by Jeren and Beus [5], the CSF findings of 84 cases with tuberculous meningitis were evalu ated, and the authors report that glucose and chloride levels were normal in a number of cases, but the protein levels were always in creased. In another series, it was reported that 17% of the cases had normal levels of CSF glucose and 25% of the cases had CSF protein levels <100 mg/dl [3], It is known that the chloride concentration CSF is dependent on the concentration of protein in the spinal fluid [6], Our patient's Cl values were normal. On admission, examination of CSF re vealed 140 WBCs with 80% mononuclear cells.…”
Section: Discussionmentioning
confidence: 50%
“…Hydrocephalus can be attributed to various factors, including CSF infection, [20,21] primary meningitis, and the post-surgery infection of a series of neurosurgical diseases. According to Arunodaya's study, [22] the post-neurosurgery nosocomial wound infection rate is 6.9%.…”
Section: Discussionmentioning
confidence: 99%